General evaluation of the economic impact of introduction of Chlamydia abortus to a Scottish sheep flock. Issue 3 (10th September 2018) - Robertson, Abigail; Handel, Ian; Sargison, Neil Donald
Abstract : The investigation of an outbreak of chlamydial abortion in a Scottish sheep flock in which there was an overall abortion rate of 12.2 per cent was used as an example to highlight the potential economic impact of the new introduction of an infectious disease. Farm accounts, excluding forage costs, were analysed for the year preceding and the year in which a chlamydial abortion outbreak occurred. The largest contributing factor to the cost of abortion was the loss of lamb sales; nevertheless, veterinary fees, investigation costs, prevention through vaccination and carcase disposal also contributed. Forage costs vary greatly between years, illustrating the need for caution in interpreting gross margin alone as an indicator of disease cost. Subsidy payments were not included in the economic analysis as they were not influenced by the disease outbreak, but it is noted that they would have buffered its impact. The estimated cost of this chlamydial abortion storm based on the comparison of overall lamb losses before and during the year following the probable introduction of Chlamydia abortus was £2163 per 100 ewes. The high estimated cost of a chlamydial abortion outbreak shown by the present study outweighs the cost of routine preventive management, involving investment in good biosecurity including sourcing replacements from accredited disease‐free sources and vaccination.